2020
DOI: 10.3390/cancers12103045
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Donors Harbor Memory T Cell Responses to RAS Neo-Antigens

Abstract: The RAS mutations are the most frequently occurring somatic mutations in humans, and several studies have established that T cells from patients with RAS-mutant cancer recognize and kill RAS-mutant cells. Enhancing the T cell response via therapeutic cancer vaccination against mutant RAS results in a clinical benefit to patients; thus, T cells specific to RAS mutations are effective at battling cancer. As the theory of cancer immuno-editing indicates that healthy donors may clear malignantly transformed cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In order to assess the immune response against CALRLong36, we used IFN-g ELISPOT assays performed on PBMCs as described in detail earlier (37). In short, PBMCs were thawed and stimulated with CALRLong36 and then stimulated with IL-2 (120 U/mL) the next day.…”
Section: Ifn-g Elispot Assaymentioning
confidence: 99%
“…In order to assess the immune response against CALRLong36, we used IFN-g ELISPOT assays performed on PBMCs as described in detail earlier (37). In short, PBMCs were thawed and stimulated with CALRLong36 and then stimulated with IL-2 (120 U/mL) the next day.…”
Section: Ifn-g Elispot Assaymentioning
confidence: 99%
“…Recently, it was reported that neoantigen-reactive T lymphocytes are also present in healthy individuals (Holmström et al 2019;Holmström and Andersen 2020). For example, the presence of T lymphocytes that respond to neoantigen peptides by K-RAS mutation was also demonstrated in healthy individuals (Holmström and Andersen 2020). The presence of neoantigen-reactive T cells before the start of immunotherapy for cancer and possibly before the onset of cancer is an interesting finding, and further research in this field is expected in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Our retrospective study also suggested the involvement of neoantigen-reactive T lymphocytes that were present before treatment. Recently, it was reported that neoantigen-reactive T lymphocytes are also present in healthy individuals (Holmström et al 2019;Holmström and Andersen 2020). For example, the presence of T lymphocytes that respond to neoantigen peptides by K-RAS mutation was also demonstrated in healthy individuals (Holmström and Andersen 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This undertaking should be aimed at examining the validity of the "3Es" (94) hypothesis. To the best of our knowledge, the presence and distribution of the immune reactivities to the mutated RAS and RAF oncoproteins in a general population has not yet been reported, although the presence of immune responses to mutated RAS epitopes has been demonstrated (83). We therefore propose to select groups of ten to twenty unvaccinated healthy volunteers belonging to different age groups (21-30, 31-40, 41-50, 51-60, and so on) for such an investigation.…”
Section: Further Research Is Needed Suggestions In Brief For Next Ser...mentioning
confidence: 96%
“…While major support for the present concept of prophylactic anti-cancer vaccine development stems from experiments in a mice model, a strong backup for this concept has quite recently been provided by the demonstration of immune responses to mutated RAS epitopes in healthy subjects (83). This provides a strong support for the assumption that these healthy individuals experienced contact with cells expressing the respective RAS mutations earlier in their lives but have been capable of effectively controlling the neoplastic process.…”
Section: Mutations In Ras Oncogene-induced Immune Responsesmentioning
confidence: 99%